Magnetic resonance imaging in non-conditional pacemakers and implantable cardioverter-defibrillators: a systematic review and meta-analysis. Issue 2 (30th January 2020) - Munawar, Dian A; Chan, Joel E Z; Emami, Mehrdad; Kadhim, Kadhim; Khokhar, Kashif; O'Shea, Catherine; Iwai, Shinsuke; Pitman, Bradley; Linz, Dominik; Munawar, Muhammad; Roberts-Thomson, Kurt; Young, Glenn D; et al.
Abstract: Aims: There is growing evidence that magnetic resonance imaging (MRI) scanning in patients with non-conditional cardiac implantable electronic devices (CIEDs) can be performed safely. Here, we aim to assess the safety of MRI in patients with non-conditional CIEDs. Methods and results: English scientific literature was searched using PubMed/Embase/CINAHL with keywords of 'magnetic resonance imaging', 'pacemaker', 'implantable defibrillator', and 'cardiac resynchronization therapy'. Studies assessing outcomes of adverse events or significant changes in CIED parameters after MRI scanning in patients with non-conditional CIEDs were included. References were excluded if the MRI conditionality of the CIEDs was undisclosed; number of patients enrolled was <10; or studies were case reports/series. 35 cohort studies with a total of 5625 patients and 7196 MRI scans (0.5–3 T) in non-conditional CIEDs were included. The overall incidence of lead failure, electrical reset, arrhythmia, inappropriate pacing and symptoms related to pocket heating, or torque ranged between 0% and 1.43%. Increase in pacing lead threshold >0.5 V and impedance >50Ω was seen in 1.1% [95% confidence interval (CI) 0.7–1.8%] and 4.8% (95% CI 3.3–6.4%) respectively. The incidence of reduction in P- and R-wave sensing by >50% was 1.5% (95% CI 0.6–2.9%) and 0.4% (95% CI 0.06–1.1%), respectively. Battery voltage reduction of >0.04 V was reported in 2.2% (95% CI 0.2–6.1%). Conclusion: This meta-analysis affirms the safety of MR imaging in non-conditional CIEDs with no death or implantable cardioverter-defibrillator shocks and extremely low incidence of lead or device-related complications. Graphical Abstract: